Angina and Future Cardiovascular Events in Stable Patients With Coronary Artery Disease: Insights From the Reduction of Atherothrombosis for Continued Health (REACH) Registry. Issue 10 (October 2016) - Eisen, Alon; Bhatt, Deepak L.; Steg, P. Gabriel; Eagle, Kim A.; Goto, Shinya; Guo, Jianping; Smith, Sidney C.; Ohman, E. Magnus; Scirica, Benjamin M.
Abstract : Background: The extent to which angina is associated with future cardiovascular events in patients with coronary artery disease has long been debated. Methods and Results: Included were outpatients with established coronary artery disease who were enrolled in the REACH registry and were followed for 4 years. Angina at baseline was defined as necessitating episodic or permanent antianginal treatment. The primary end point was the composite of cardiovascular death, myocardial infarction, or stroke. Secondary end points included heart failure, cardiovascular hospitalizations, and coronary revascularization. The independent association between angina and first/total events was examined using Cox and logistic regression models. Out of 26 159 patients with established coronary artery disease, 13 619 (52%) had angina at baseline. Compared with patients without angina, patients with angina were more likely to be older, female, and had more heart failure and polyvascular disease ( P <0.001 for each). Compared with patients without angina, patients with angina had higher rates of first primary end‐point event (14.2% versus 16.3%, unadjusted hazard ratio 1.19, CI 1.11–1.27, P <0.001; adjusted hazard ratio 1.06, CI 0.99–1.14, P =0.11), and total primary end‐point events (adjusted risk ratio 1.08, CI 1.01–1.16, P =0.03). Patients with angina were at increased risk for heart failure (adjusted odds ratio 1.17, CI 1.06–1.28, P =0.002), cardiovascular hospitalizations (adjusted odds ratio 1.29, CI 1.21–1.38, P <0.001), and coronary revascularization (adjusted odds ratio 1.23, CI 1.13–1.34, P <0.001). Conclusions: Patients with stable coronary artery disease and angina have higher rates of future cardiovascular events compared with patients without angina. After adjustment, angina was only weakly associated with cardiovascular death, myocardial infarction, or stroke, but significantly associated with heart failure, cardiovascular hospitalization, and coronary revascularization.